(untitled) (Research, Society and Development, 2022)
Objective. To predict when different countries will reach 70% of fully vaccinated population against COVID-19 and to assess the effects of vaccine rejection on the number of patients admitted to ICU and on rates of omicron and other SARS-Cov-2 variants infections. Methods. Data on the ‘number of patients with COVID-19 admitted to ICU’, ‘share of people who received at least one dose of COVID-19 vaccine’ and ‘percentage of unvaccinated population (USA, Brazil, Europe, Africa, Asia) that refuses to receive the first dose of COVID-19 vaccine’ were collected from a public database from December 2020-January 2022. Time series-based models were used to predict when countries will reach 70% rate of fully vaccinated population. Results. ARIMA model was robust for predicting COVID-19 vaccination in different countries. In the USA, Brazil, the European Union and Asia 70% of the population was vaccinated against COVID-19 between September 2021-April 2022. In the Africa, the forecast is only in the beginning of 2024. The percentage of the unvaccinated population had a significant effect on the increase in ICU admissions and on the increase of omicron, alpha, delta, and gamma variant cases. Conclusion. Although the ARIMA model showed the best performance to predict vaccination patterns, its accuracy may decrease over time especially due the vaccination rejection rate. In this scenario, strategies to improve vaccination should be implemented.